Cabbage Palm Caterpillar, Litoprosopus futilis (Grote & Robinson) (Insecta: Lepidoptera: Noctuidae: Ophiderinae) - G. W. Dekle (EDIS)
Revised! EENY-095, a 4-page illustrated fact sheet by G. W. Dekle, is part of the Featured Creatures collection. It describes this larva of the owlet moth that can seriously affect the production of palmetto honey — synonymy, distribution, description, hosts, field observations, economic importance, and management. Includes references. Published by the UF Department of Entomology and Nematology, April 2010.